Strategic variables of commercialization of renewable energy technologies - Aslani, Alireza (AIP Publishing, 2015)
Utilization of renewable energy sources, as domestic and local natural resources, has important role among the energy policies of the governments. However, diffusion of renewable energy technologies have faced with challenges that slow the development plans and affect security of energy supply. As commercialization is an important contributor to successful diffusion and adaptation of a technology, this research studies the role of commercialization of renewable energy technologies and identifies the key factors of commercialization. A decision matrix is also presented to show the best government strategies for successful commercialization of renewable energy products and services. The contributions help researchers and policy makers to focus more on the strategic variables of commercialization of renewable energy technologies.
Keywords: energy technology; renewable energy sources; energy production (process industry); commercialisation (activity); sources of energy; energy; markets (systems); sustainable development; technology; Finland; fi=Tuotantotalous|en=Industrial Management|